17+9s=2(8s-3)

Simple and best practice solution for 17+9s=2(8s-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17+9s=2(8s-3) equation:


Simplifying
17 + 9s = 2(8s + -3)

Reorder the terms:
17 + 9s = 2(-3 + 8s)
17 + 9s = (-3 * 2 + 8s * 2)
17 + 9s = (-6 + 16s)

Solving
17 + 9s = -6 + 16s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-16s' to each side of the equation.
17 + 9s + -16s = -6 + 16s + -16s

Combine like terms: 9s + -16s = -7s
17 + -7s = -6 + 16s + -16s

Combine like terms: 16s + -16s = 0
17 + -7s = -6 + 0
17 + -7s = -6

Add '-17' to each side of the equation.
17 + -17 + -7s = -6 + -17

Combine like terms: 17 + -17 = 0
0 + -7s = -6 + -17
-7s = -6 + -17

Combine like terms: -6 + -17 = -23
-7s = -23

Divide each side by '-7'.
s = 3.285714286

Simplifying
s = 3.285714286

See similar equations:

| 30-5(p-10)=11 | | 16x^2+3=-16x | | -14=4p+7-3p | | 6x+10=2y+10 | | -14=-8p+5+9p | | (x+1)/(2-x)*(2-x)^2/(x-2)*2/x+1 | | -11w+6=-38 | | .24.14= | | 10=-2p-2+3p | | -4=-4p-11+5p | | M/-16=-9 | | y-9=15(x-5) | | 13=3p-15-2p | | x^2+24x-23=0 | | 8x^2-28x+98=0 | | 8x^2-28+98=0 | | 38x-14=20 | | 2(x-2)=-3x+21 | | 2+3.8= | | 3(2a-4)= | | 2(x-2)=-3+21 | | 3a+50=140 | | -9-6=8+x | | (y^2-7)(5y^2-5y+6)= | | 2+38= | | -13=7p-12-6p | | 36r^9-9r^6+54r^3= | | 7(3x-4)=17x | | x+6/5+x-1/4=2 | | 11=8p-14-7p | | n^2=4n+5 | | 1/2y-1/3x-1=0 |

Equations solver categories